2017
DOI: 10.3390/polym9050164
|View full text |Cite
|
Sign up to set email alerts
|

Syneresis in Gels of Highly Ferulated Arabinoxylans: Characterization of Covalent Cross-Linking, Rheology, and Microstructure

Abstract: Arabinoxylans (AXs) with high ferulic acid (FA) content (7.18 µg/mg AXs) were cross-linked using laccase. Storage (G') modulus of AX solutions at 1% (AX-1) and 2% (AX-2) (w/v) registered maximum values of 409 Pa and 889 Pa at 180 min and 83 min, respectively. Atomic force microscopy revealed the grained and irregular surface of the AX-1 gel and the smoother surface without significant depressions of the AX-2 gel. Cured AX gels exhibited a liquid phase surrounding the samples indicating syneresis. The syneresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
23
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 24 publications
15
23
2
Order By: Relevance
“…The protein content in AX was 8.2%, which is similar to the values previously obtained for another maize AX . AX has a high FA content (7.53 μg/mg AX), which is similar to the recent value reported by Morales‐Burgos et al . for maize bran AX (7.18 μg/mg AX).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The protein content in AX was 8.2%, which is similar to the values previously obtained for another maize AX . AX has a high FA content (7.53 μg/mg AX), which is similar to the recent value reported by Morales‐Burgos et al . for maize bran AX (7.18 μg/mg AX).…”
Section: Resultssupporting
confidence: 90%
“…A residual amount of glucose in AX was also quantified, which was similar to the previous reports for maize bran AX . It has been reported that maize bran AX presents a complex structure and may contain small amounts of galactose, mannose, glucuronic acid, and other hydroxycinnamic acids such as coumaric acid . The protein content in AX was 8.2%, which is similar to the values previously obtained for another maize AX .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Previous reports for AX microspheres presented a q of 18 g H 2 O/g AX with equilibrium being reached ~8–12 min . This difference in swelling ratios could be explained from the higher amount of FA covalent crosslinks and the more compact structure presented in highly ferulated AX gels that restricts the swelling . The data acquired from the swelling experiments allow calculating the structural parameters of the gels using the Flory and Rehner model modified by Peppas and Merrill .…”
Section: Resultsmentioning
confidence: 99%